Особливості адміністративної відповідальності за делікти у сфері банківської діяльності - Букрєєв, М. Ю.; Bukreev, M. Yu.; ORCID: https://orcid.org/0000-0002-9863-3660 (Право і безпека. – 2018. – № 2 (69). – С. 18-22, 2018)
Проаналізовано вітчизняні дослідження у науці адміністративного права з метою визначення поняття та виокремлення специфічних ознак адміністративної відповідальності за делікти у сфері банківської діяльності. Розглянуто наукові підходи до визначення адміністративної відповідальності за делікти у сфері банківської діяльності. Окреслено наукові теорії, які дають тлумачення адміністративної відповідальності за делікти у сфері банківської діяльності, та сформульовано специфічні ознаки, властиві адміністративній відповідальності у сфері банківської діяльності.

The article is focused on scientific problems of administrative law. The author analyzed the scientific notions of administrative responsibility. The author gave a definition of administrative responsibility for administrative delicts within banking operations. The author identified specific features of administrative responsibility within banking operations. The article deals with the scientific approaches to the definition of responsibility for administrative delicts within banking operations. The author, with the help of the deductive method, outlines the scientific theories that interpret the responsibility for administrative delicts within banking operations. The author of the article substantiates the theory of responsibility for administrative delicts within banking operations, namely: security, punitive, management, coercion, obligation, conviction. The author considers the features that are inherent for administrative responsibility within banking operations. The author names specific features that are inherent for administrative responsibility within banking operations, namely: small public harm is based on normative, factual and procedural grounds, has negative consequences for delinquency, is accompanied by public condemnation of delicts, does not involve cryptography. It has been concluded that administrative responsibility for delicts within banking operations is the application of enforcement action for a delinquent offender (an individual or a legal entity) for the violation of banking legislation by the National Bank of Ukraine that are stipulated by the relevant administrative and legal norm. Responsibility for administrative delicts within banking operations is an element of state management mechanism, challenged to restore violated legal relations within banking operations that is protected by the relevant administrative and legal norm by imposing administrative fines for a delinquent offender.

Проанализированы отечественные исследования в науке административного права с целью определения понятия и выделения специфических признаков административной ответственности за административные деликты в сфере банковской деятельности. Рассмотрены научные подходы к определению административной ответственности за деликты в сфере банковской деятельности. Очерчены научные теории, дающие толкование административной ответственности за деликты в сфере банковской деятельности и сформулированы специфические признаки, свойственные административной ответственности в банковской деятельности.
Responsibility for administrative delicts within banking operations
Ответственность за административные деликты в сфере банковской деятельности
Букрєєв, М. Ю. Особливості адміністративної відповідальності за делікти у сфері банківської діяльності / Букрєєв Михайло Юрійович // Право і безпека. – 2018. – № 2 (69). – С. 18-22.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; адміністративна відповідальність; адміністративні делікти; банківська діяльність; административная ответственность; административные деликты; банковская деятельность; administrative responsibility; administrative delicts; banking operations